Metaphors in William Shakespeare’s Play Hamlet - Syamsul Bahri; Joys Andrean Mardohar Sitanggang; Shinta Melina Sidabutar (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
Metaphors were mosly found in the drama “Hamlet.” It confused and made it hard for the readers to understand some dialogue in that drama. It became an interesting one to explore more profound about the use of metaphors. This study explored more the metaphors in the conversation among characters in William Shakespeare’s play Hamlet. The researcher applied a qualitative descriptive method with the theory of the Metaphor, according to Parera (2004), as a detailed explanation. The study results found that the most frequently occurring types were Animal Metaphors (35%), and Anthropomorphic Metaphors as the rarest one (15%). Animal Metaphor uses animal parts to mock people in this story. Anthropomorphic metaphors are parts of the human body that are transferred to various inanimate objects used to praise in this story. Metaphors occured in a drama which can make it more interesting to read and perform